Mass shootings: media, myths, and realities - Schildkraut, Jaclyn (Crime, media, and popular culture, 2016)
Claims making and agenda setting: how myths become realities -- What is a "mass shooting"? -- A history of public mass shootings -- Mass shootings by the numbers -- The "usual suspects" as causal factors -- Mass shootings around the globe -- Preventing mass shootings -- Mass shootings in a mediated society -- Mass shootings today--and beyond